Digital Life Middle-Class on Instagram: Like, Share and Comment - Kertamukti, Rama; Nugroho, Heru; Wahyono, S. Bayu (KnE Social Sciences, 2019)
Instagram, today as a result of technology that is acculturated with economic, social and cultural factors, brings leisure to the middle class, they do activities freely in life such as hobbies, recreation. The middle class in accessing Instagram is reduced by the Instagram algorithm to be a one-dimensional human. The middle class will be a uniform individual with the same activities like share, and comment. The middle class is a lasting individual who runs consumerism where everything becomes a commodity and is trapped in relations in the algorithm of relationships made by Instagram. For the middle-class Instagram is a lifestyle and daily activity. Instagram, which is mediated via cell phone, is a new socialization space that frees someone from the rules and disciplines of the patriarchal system. This activity results in the middle class recognizing, embracing and exploring things that cannot be expressed in everyday reality. Instagram in the middle class produces digital life practices that want to show a lifestyle. This study examines the phenomenon of middle-class practice in showing the practice of digital life: like share and comment on Instagram. Researchers will use a virtual ethnographic method. The virtual ethnographic approach will be carried out because this research is an object in cyberspace so that it can adequately understand the way the subject interacts and collaborates through observed phenomena. Instagram is a photo showroom, a kind of private space because the user gallery can be designed in such a way as the user wishes, users upload whatever happens around them, which is considered to represent user activity. The three accounts examined by @fajarmantoo, @herni_maryuliani and @ rosakusumaazhar present activities in digital life. The fact that manifests these two accounts is that consumption and production in the Instagram arena provide the formation of social reality. Instagram becomes a social reality forming tool that can give an idea of how activities in the middle class when on Instagram. Keywords: digital life, Instagram, Middle Class